149 Differences in Gene Expression Following Natural Exposure to Gastrointestinal Parasites between Sheep Selected for High Innate Responses and High Antibody-Mediated Adaptive Immune Responses. (21st September 2022) - Willoughby, Olivia B; Borkowski, Emma; Dixon, Samantha; Cunha, Samla Marques; Asselstine, Victoria; Perergrine, Andrew S; Menzies, Paula I; Karrow, Niel A; Cánovas, Angela
Abstract: Parasitism by gastrointestinal nematodes (GINs) is a major source of morbidity and mortality for sheep flocks grazed on pasture. Since there is evidence for genetic resistance to GINs in some sheep breeds, genetic selection for immunologic resistance to GIN is a possible management strategy. This study sought to identify differences at the transcriptome level between Ridau-Arcott sheep characterized as high innate immune responders (IIRs, n=5) or high antibody-mediated immune responders (AbMIRs, n=5) following natural exposure to and infection with GINs after spending the summer on GIN-infested pasture; infection was confirmed with individual fecal egg counts. The transcriptomes of the high IIR and high AbMIR animals were also compared with GIN-naïve sheep of the same breed (all medium IIR and AbMIR responders, n = 7). Liver tissue samples from the 17 animals were used to perform transcriptomic analyses using RNA-Sequencing technology. The CLC Genomics Workbench 20.0.4 (CLC Bio, Aarhaus, Denmark) software was used to map reads to the most recent ovine reference genome (Oar rambouillet.v1.0.105), and for differential gene expression analysis. In total, 144 differentially expressed genes (DEG) were found between the high IIRs and the high AbMIRs (FDR< 0.05, and fold change (FC) abs > 2). When compared to the naïve animals, 136 and 53 DEG were found between them and the high IIRs and the high AbMIRs, respectively. In order to verify their function in the host immune response to GINs, functional enrichment analyses were performed on these candidate genes using the AmiGO2 software. Monocarboxilic acid metabolism was identified as an enriched biological process (FDR < 0.05), and ammonia-lyase activity and metalloendopeptidase activity were enriched molecular functions between the high IIR and high AbMIR animals (FDR < 0.05). These preliminary results improve understanding of how host resistance to GINs is genetically regulated through the innate and adaptive immune systems in sheep.